Perceived stress among university students during COVID-19 outbreak - Nur Shakila Ibharim,; Junaidah Yusof,; Divya Rose Peter, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The COVID-19 pandemic has negatively impacted the mental health of people around the world, including Malaysia. Students' mental health in higher education has been an increasing concern as they face many challenges with the changes in their educational experience. The study examines the perceived stress level among university students during the outbreak. This is the first study to use a convenience sampling technique to analyze data from 305 Malaysian university students. IBM SPSS 23.0 was used to analyze descriptive data and provide an analysis of the results. The majority of those who participated in this study were undergraduate students at age 21 years old. The pandemic affected 181 of their family's earnings, while the remaining 124 were unaffected. Out of 305 respondents, 131 (42.9%) of them have stress in an extremely severe state. It followed by 68 respondents in a state of severe stress. Simultaneously, 47 (15.4%) of them are at the normal state of stress and 32 (10.5%) respondents in mild stress. The result shows that only 27 (8.9%) of the respondents have moderate stress. It is believed that the main factors associated with students' perceived stress level are home-based online learning and financial constraints.